Tourism Search Application within the Bima City Locale of West Nusa Tenggara Utilizing the Android-Based Location-Based Benefit Strategy Utilizing Visual Studio Code - Turrahman, Fitrah; Faizah, NM; Koryanto, Lucky (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Bima is one of the cities in West Nusa Tenggara which has various tourist objects. Apart from nature tourism, there are also many other tours such as modern water tourism that provides water parks, historical tours, religious tours and culinary tours. So far, recommendations for tourist destinations are usually word of mouth, mass media, browsing¸ and social media. This makes not all tourist objects can be visited, due to lack of information and the location of tourist objects that are scattered so that it is difficult to reach by public transportation. This research offers an android application that can provide convenience to tourists who want to visit tourist attractions. This application provides information about existing tourist objects starting from location information, facilities, opening and closing hours as well as guides for reaching locations using the Location Based Service method. Every tourist can download the application and run it on a smartphone. Application users can select tourist objects by category and the system will provide guide facilities to the tourist sites they want to visit. This application is expected to be a solution to the problems above and become a media for tourism promotion in the city of Bima.